ANALISIS PENERAPAN GREEN CAMPUS BERDASARKAN UI GREENMETRIC PADA FAKULTAS TEKNIK UNIVERSITAS PATTIMURA AMBON - Pertiwi, Hana; Buyang, Christy Gery; Sangadji, Fauzan A (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The University of Indonesia launched the UI GreenMetric World University Ranking in 2010 as a benchmark for evaluating green campuses. The goal of the college community's